The spirituality of bishop Karol Wojtyla - John Paul II in his own notes - Jan Machniak (Polonia Sacra)
Private notes of Karol Wojtyła – John Paul II just on the moment of death of their author excited big interest between the people. The pope wrote in the testament, his secretary Msgr. Dziwisz has to fire all the documents, he left. Card. Stanisław Dziwisz didn’t accomplish the will of pope, because he was convinced, it is very important document, showing the interior life of John Paul II. Recently, the Publishing House Znak printed this Private notes (Krakow 2014) giving to the publicity to know the spiritual life of Karol Wojtyła – John Paul II. The Private notes are some kind of “diary of the soul” showing deeper life with God of Karol Wojtyła as bishop of Krakow, cardinal and pope. They are giving the possibility to enter in the mystery of the soul of John Paul II, to know his life of prayer, meditation and his relation to God and to Blessed Virgin Mary.